The protective gene dose effect of the APOEε2 allele on gray matter volume in cognitively unimpaired individuals. Issue 7 (8th December 2021) - Salvadó, Gemma; Ferreira, Daniel; Operto, Grégory; Cumplido‐Mayoral, Irene; Arenaza‐Urquijo, Eider M.; Cacciaglia, Raffaele; Falcon, Carles; Vilor‐Tejedor, Natàlia; Minguillon, Carolina; Groot, Colin; van der Flier, Wiesje M.; Barkhof, Frederik; et al.
Abstract: Introduction: Harboring two copies of the apolipoprotein E ( APOE ) ε2 allele strongly protects against Alzheimer's disease (AD). However, the effect of this genotype on gray matter (GM) volume in cognitively unimpaired individuals has not yet been described. Methods: Multicenter brain magnetic resonance images (MRIs) from cognitively unimpaired ε2 homozygotes were matched (1:1) against all other APOE genotypes for relevant confounders (n = 223). GM volumes of ε2 genotypic groups were compared to each other and to the reference group ( APOE ε3 / ε3 ). Results: Carrying at least one ε2 allele was associated with larger GM volumes in brain areas typically affected by AD and also in areas associated with cognitive resilience. APOE ε2 homozygotes, but not APOE ε2 heterozygotes, showed larger GM volumes in areas related to successful aging. Discussion: In addition to the known resistance against amyloid‐β deposition, the larger GM volumes in key brain regions may confer APOE ε2 homozygotes additional protection against AD‐related cognitive decline.